Skin Microbiota of the Captive Giant Panda (Ailuropoda Melanoleuca) and the Distribution of Opportunistic Skin Disease-Associated Bacteria in Different Seasons - Ma, Xiaoping; Li, Gen; Yang, Chao; He, Ming; Wang, Chengdong; Gu, Yu; Ling, Shanshan; Cao, Sanjie; Yan, Qigui; Han, Xinfeng; Wen, Yiping; Zhao, Qin; et al. (Frontiers in Veterinary Science, 2021)
The giant panda (Ailuropoda melanoleuca) is one of the rarest animals in the world (Ma et al., 2017). Skin diseases that seriously endanger the health of this animal are considered the second major cause of its morbidity. Skin microbiota is a complex ecosystem, and the community structure and the pathogenic potential of bacteria on giant panda skin remain largely unclear. In order to understand the skin bacterial flora of captive giant pandas, the microbiota in giant panda skin samples collected during different seasons were profiled via 16S rRNA gene sequencing. In total, 514 genera from 50 bacterial phyla were detected, with Proteobacteria (40.5%), Actinobacteria (23.1%), Firmicutes (21.1%), Bacteroidetes (9.5%) , Cyanobacteria (2.1%), and Thermi (1.2%) as the predominant phyla, and Streptococcus (13.9%), Acinetobacter (9.2%), Staphylococcus (2.9%), Pseudomonas (5.9%), Dermacoccus (4.8%), Brachybacterium (2.9%), and Escherichia (2.7%), Chryseobacterium (2.1%), Arthrobacter (1.6%), Kocuria (1.5%), Psychrobacter (1.2%), Deinococcus (1.1%), and Flavobacterium (1.1%) as the predominant genera. The results indicated that species diversity was lower in winter than in other seasons and higher in autumn than in other seasons. Species abundance in spring was significantly higher than that in other seasons. Several bacterial genera associated with skin diseases, including Streptococcus, Staphylococcus, Acinetobacter, Pseudomonas, Arthrobacter and Propionibacterium, were detected in the bacterial flora of healthy giant pandas. Skin disease-associated bacteria are normal components of skin bacterial flora. To our knowledge, ours is the first study to reveal the diversity of skin bacterial communities in captive giant pandas and provide insights into the development of skin diseases in captive giant pandas.